ANALISA FAKTOR MINAT SISWA UNTUK MELANJUTKAN KE PERGURUAN TINGGI DI SMK NEGERI 2 KABUPATEN TANJUNG JABUNG TIMUR - Sri Handayani; Pratiwi Indah Sari (SJEE (Scientific Journals of Economic Education), 2023)
This study aims to find out what factors are involved and are most dominant in influencing class XII students of SMK Negeri 2 Tanjung Jabung Timur Regency to continue their studies in tertiary institutions. In this study the authors used descriptive research methods and factorization analysis. This factor analysis does not classify variables into categories of independent and dependent variables but instead looks for interdependence relationships between variables in order to identify the dimensions or factors that compose them. The results showed there are several factors that exist, namely individual factors, environmental factors, higher education institution factors and brochure factors, with the value of KMO (Kaiser-Meyer-Olkin) Measures of Sampling Adequacy is 0.407 with a significance value of 0.004. Meanwhile, the value of Bartlett's Test of Sphericity is 6. Thus, it can be seen that from the results of the analysis that has been carried out and based on the Table of Measures of Sampling Adequacy values for each research variable, the component is more dominant with an acquisition value of 0.348 (individual factor). Keywords : Student Interest, College